Patterns of maxillofacial fractures in relation to helmet usage and velocity among motorcyclist - Tahrin, Mior Faiq Mior Abu (2020)
Introduction Significant number in road traffic accidents in Malaysia involve motorcyclists, and facial injuries poses serious functional, physiological and aesthetical problems. One of the contributing factors in sustaining debilitating injuries are speeding and non-compliance to the usage of safety helmets. The aim of this study is to determine the patterns of maxillofacial injury among motorcyclists according to helmet usage, different types of helmets used, and cruising velocity of the motorcycle. Method This was a cross sectional study that evaluates the patterns of maxillofacial injuries sustained following road traffic accidents among motorcyclists. A total of 163 patients were recruited into this study which were then grouped into five categories (unhelmeted, fullfaced, modular, open-faced, and half-helmet). Convenience sampling was used in this study to recruit all the motorcyclists that presented to the Emergency Department, or those who was referred as an outpatient to the clinic. Maxillofacial injury was then determined based on clinical and radiological examination and then categorized into upper, midface and lower face fractures. Specific proforma was used for data collection. Result A total of 143 males and 20 females were involved in an accident in this study. Among all the races, Malay had the highest involvement (85.3%), followed by Indians (7.4%), Chinese (3.7%) and others (3.7%). The three most common mechanisms of injuries were motorcycle vs car, single-vehicle collision (skidded), and motorcycle vs motorcycle. In general, injuries were seen mainly on midface (41.7%), followed by a combination of upper and mid face (20.2%), combination of midface and lower face (16%) and others (22.1%). There was no association between helmet usage and pattern of maxillofacial fracture (p>0.05). There was also no association between pattern of maxillofacial fractures and velocity (p> 0.05). Conclusion Helmet usage, the types of helmet used, and velocity do not influence the pattern of maxillofacial injuries among motorcyclists following road traffic accidents. However, a helmet of any type that is correctly worn and remains secured on the head throughout a crash will provide some form of protection against head and facial injury.